LITERSI SEBAGAI IDE PENCIPTAAN KARYA SENI PAPERCUT - Nasruddin, Indra Aryani Nasti (IAIIG Cilacap, 2019)
As we know literacy is the source of science the more we are literate the more we know with the development of technology, litersipun also develops. We can no longer simply call literacy relating only to reading and writing letters and numbers. Because the letters and numbers are basically the means of carrier, delivery and storing information. Now, the information we get not only through letters and numbers. However, for the information presented through television broadcasts, we not only need the ability to read letters and numbers but also to read television, commonly called media literacy. This condition creates a challenge for us all to be able to live in a new world called the world of shortness of media, as well as the world whose communication antarmanusiannya increasingly relies on information and communication technology.In this creation, the method used starts from the exploration stage by exploring the theme of